The vocal competence of children and youth - diagnostic research - Kamińska, Barbara (Interdisciplinary Studies in Musicology, 2018)
There is a prevailing conviction that Poles cannot sing. The custom of singing has died out in families, and it is even waning in music lessons in school. There is a general perception that singing skills are conditioned by the possession of special musical abilities and that not everyone can master them. This article presents the results of my diagnostic research carried out at the end of the 1980s and reprised by other scholars in recent years. Because the same research method and procedures were used in all this research, it is possible to compare the results and observe any changes in the level of singing skills over the space of around twenty years. The research signals an alarming situation in respect to such an important musical competence as singing. After the twenty years that have passed since the first research, we observe a decline in the ability to sing among children and youngsters.